al-ʻĀlam wa-al-gharb : al-taḥaddī al-Ūrūbī wa-al-instijābah fīmā warāʼ al-baḥār fī ʻuṣūr al-imbirāṭūrīyāt - Curtin, Philip D.; Curtin, Philip D. (K-Tab.net, 2010)
The World and the West reaches from such diverse cases as the Maya and Yaqui of Mexico, the Ghost Dance of North America, cargo cults of Melanesia, to Meiji Japan and the Ottoman Empire. In discussing a variety of questions about the relations between the world and the West in recent centuries, Curtin ultimately introduces a new perspective on the underlying question: How do human societies change through time?